Economic impacts of infrastructure investment with different funding mechanisms: evidence from Guinea-Bissau - Júlio Vicente Cateia; Luc Savard; Clailton Ataídes de Freitas (Cogent Economics & Finance, 2022)
This study aims to analyze the economic impacts of infrastructure investment in Africa, focusing on the Guinea-Bissau economy. Through a dynamic CGE model, we find that the natural resource revenues (or aid)-funded infrastructure investments generate externalities that increase factor returns. The private investment improvements propagate externalities effects on GDP and job opportunities outcomes. Household income and consumption were positively impacted, though the poorer benefited the most. The income inequality has reduced. However, funding by the mix of debt and direct taxes produces opposite effects. We suggest a potential pro-poor growth agenda in Africa.
Keywords: C68; H54; O12; 330; infrastructure investment; poverty alleviation; CGE modeling; African economies; applied economics